Environmental Impact Analysis (AMDAL): Its Role and Importance in Environmental Management - Yunita Ayu; Abdur Rohman (Penerbit Hellow Pustaka, 2025)
Environmental Impact Analysis (AMDAL) is a vital instrument in environmental management in Indonesia. Regulated by law, AMDAL functions as an early prevention against negative impacts of development. The development of regulations, from PP No. 29 of 1986 to PP No. 27 of 2012, shows the government's commitment to adjusting policies to the dynamics of development and environmental protection. AMDAL is not only a legal requirement, but also a tool to support government decision-making involving community participation. AMDAL ensures sustainable development by considering social, economic, cultural, and environmental aspects. Its success depends on proper preparation, implementation of continuous mitigation, and consistent monitoring. Therefore, AMDAL is a crucial environmental risk management tool for responsible and sustainable development in Indonesia. Effective implementation of AMDAL requires commitment from all parties.